Use of ketamine in treatment-resistant depression: an integrative review (Research, Society and Development, 2022)
Depression is a disease that has appeared commonly and very frequently nowadays, however, it promotes disabling results in the minds of individuals in a global context. Given the above, the present study aims to analyze the effectiveness of the use of ketamine in patients with treatment-resistant depression. This is an integrative literature review, carried out in the SCIELO, LILACS, PubMed and CAPES Portal databases, during the period of September and October 2022, using the following descriptors “KETAMINE”, “TREATMENT-RESISTANT DEPRESSIVE DISORDER” and “THERAPEUTIC”, in addition, the descriptors were joined by the connectives “AND” and “OR”. Articles available in full, free of charge and published between 2015 and 2022 were used as inclusion criteria. As exclusion criteria, articles that do not address the issue of the use of ketamine in institutionalized treatment-resistant depression, duplicate studies and literature reviews . After collection through the established criteria, six articles were chosen, considering that they presented a random choice regarding the participants and the control group for the use of ketamine for the treatment of treatment-resistant depression. It is concluded that ketamine presented itself as a drug that presents a positive response for the treatment of treatment-resistant depression, in addition to presenting a rapid response and with few adverse effects. However, it is necessary to point out that although some tests had a small number of participants in their clinical trials, these trials described an inconsistent action of ketamine in relation to changes in the mood of the participants.